Pathways to democratization in personalist dictatorships. Issue 1 (2nd January 2017) - Frantz, Erica; Kendall-Taylor, Andrea
ABSTRACT: Personalist dictatorships make up an increasingly large proportion of the world's dictatorships. Moreover, they tend to be particularly resistant to democratization. Understanding the conditions that increase the likelihood of democratic transitions in personalist contexts, therefore, is critical for the study and practice of democratization in the contemporary era. This study argues that political party creation is a key factor. Though personalist dictators typically create parties to offset immediate threats to their power posed by the elite – and particularly the military – doing so encourages peaceful mass mobilization and a realignment of elite networks. These dynamics, in turn, enhance prospects of democratization. Using cross-national empirical tests that address the potential endogeneity of this relationship, we find support for the argument that personalist dictators who create their own political party are more likely to democratize than those who ally with a pre-existing party or rule without one.